Crystallized glass
By adding α-white silica and lithium disilicate to the glass and performing heat treatment, high-hardness crystallized glass is formed, which solves the problem of insufficient hardness in smart phones and other devices, and achieves higher hardness glass materials.
Patent Information
- Application Number
- CN202380067158.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-22
- Filing Date
- 2023-08-10
- Publication Date
- 2025-04-29
AI Technical Summary
For purposes such as smart phones, higher hardness glass is needed to deal with external shocks.
By adding a specific composition of α-white silica and lithium disilicate to the glass and subjecting heat treatment, a crystallized glass containing these main crystalline phases is formed, thereby increasing its hardness.
It achieves higher hardness crystallized glass, suitable for components of smart phones, tablets and other portable electronic devices, as well as protective protective devices for cars and aircraft, etc.
Smart Images

Figure BDA0005318392960000121 
Figure BDA0005318392960000131 
Figure BDA0005318392960000141
Abstract
Description
Technical Field
[0001] The present invention relates to a crystallized glass, in particular to a hard crystallized glass. Background Art
[0002] In recent years, in order to increase the freedom of design in the appearance of smartphones, glass components have begun to be used for their cover glasses and housings. These glass components are required to be scratch-resistant and not easily broken even when impacted by external factors such as when a smartphone is dropped on asphalt.
[0003] As the strength and hardness glass that have improved glass, there is crystallized glass. Crystallized glass is to make crystallization separate out in the glass interior and obtain, and it is known that its mechanical strength is more excellent than amorphous glass. In addition, it is also known that the compressive stress layer can be formed on the surface to improve strength and hardness by modes such as chemical strengthening.
[0004] Patent Document 1 discloses a glass ceramic material that is capable of rapid ion exchange, has high fracture toughness, is transparent or translucent, and has a petalite crystalline phase and a lithium silicate crystalline phase.
[0005] Patent Document 2 discloses a tempered crystallized glass containing α-cristobalite.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2021-095333
[0009] Patent Document 2: Japanese Patent Application Publication No. 2022-044054 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, in applications such as glass parts for smartphones, glass with higher hardness is required.
[0012] Solutions to technical problems
[0013] The object of the present invention is to provide a hard crystallized glass.
[0014] The inventors of the present invention have conducted active research and found that by heat treating a glass having a specified composition under specified conditions, a crystallized glass containing both α-white silica and lithium disilicate as the main crystal phase can be obtained, and further by adding lithium disilicate to α-white silica, the hardness can be improved. In addition, it is found that although the crystallized glass containing lithium disilicate as the main crystal phase is difficult to be chemically strengthened in two stages, it is easy to be chemically strengthened in two stages as long as it is a predetermined composition and main crystal phase. The present invention is completed based on these findings.
[0015] The present invention provides the following products.
[0016] (Composition 1)
[0017] A crystallized glass comprising: α-white silica as a main crystal phase, and lithium disilicate;
[0018] Calculated in mass % of oxide conversion:
[0019] The content of SiO2 component is 65.0% to 85.0%;
[0020] The content of Al2O3 component is 1.5% to 5.9%;
[0021] The content of P2O5 component is greater than 0% and less than 5.0%;
[0022] The content of Li2O component is 5.0% to 10.8%; and
[0023] The content of ZrO2 component is 4.0% to 12.5%; and
[0024] [(SiO2 content + Li2O content) / Al2O3 content] is greater than 13.9.
[0025] (Composition 2)
[0026] The crystallized glass according to composition 1, wherein, in terms of mass % as oxides:
[0027] The content of B2O3 component is 0% to 5.0%;
[0028] The content of Na2O component is 0% to 5.0%;
[0029] The content of K2O component is 0% to 5.0%;
[0030] The content of MgO component is 0% to 5.0%;
[0031] The content of CaO component is 0% to 5.0%;
[0032] The content of ZnO component is 0% to 5.0%;
[0033] The content of TiO2 component is 0% to 5.0%;
[0034] The content of Gd2O3 component is 0% to 5.0%;
[0035] The content of Sb2O3 component is 0% to 3.0%; and
[0036] The content of Nb2O5 component is 0% to 3.0%.
[0037] (Composition 3)
[0038] The crystallized glass as described in Composition 1 or Composition 2, wherein the content of ZrO2 component is 4.7% to 12.5%.
[0039] (Composition 4)
[0040] The crystallized glass as described in any one of Compositions 1 to 3, wherein the content of the ZrO2 component is greater than 7% and less than 12.5%.
[0041] (Composition 5)
[0042] The crystallized glass according to any one of Compositions 1 to 4, wherein, in terms of mass % as oxides:
[0043] [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] is less than 0.88.
[0044] (Composition 6)
[0045] The crystallized glass according to any one of Compositions 1 to 5, wherein, in terms of mass % as converted to oxides:
[0046] [(content of P2O5 component + content of K2O component + content of MgO component + content of Al2O3 component) / content of ZrO2 component] is less than 1.32.
[0047] (Composition 7)
[0048] The crystallized glass according to any one of Compositions 1 to 6, which has a compressive stress layer on the surface.
[0049] (Composition 8)
[0050] The crystallized glass according to any one of Compositions 1 to 7, wherein the crystallized glass can be used for glass components of smartphones.
[0051] Effects of the Invention
[0052] According to the present invention, hard crystallized glass can be provided.
[0053] The crystallized glass of the present invention can be used as a component of a housing of a smartphone, a tablet computer, a wearable terminal or other portable electronic device due to its high hardness, or as a component of a protective shield used in a transportation body such as a car or an airplane, a substrate for a head-up display or the like. DETAILED DESCRIPTION
[0054] Hereinafter, embodiments and examples of the crystallized glass of the present invention will be described in detail, but the present invention is not limited to the following embodiments and examples, and can be implemented with appropriate changes within the scope of the purpose of the present invention.
[0055] In this specification, the content of each component is expressed in mass % of oxide conversion unless otherwise specifically denied. Wherein, "oxide conversion" means that when it is assumed that all the components of the crystallized glass are decomposed into oxides, the value of the amount of oxides of each component contained in the crystallized glass when the total mass of the oxide is set to 100 mass % is expressed in mass %. In this specification, A% to B% are expressed as more than A% and less than B%.
[0056] The crystallized glass of the present invention comprises α-white silica as the main crystal phase and lithium disilicate. The present invention further improves the hardness compared with the crystallized glass containing α-white silica but not containing lithium disilicate by simultaneously including these crystal phases in the prescribed composition. The crystal phase also comprises a solid solution.
[0057] In the present invention, "main crystalline phase" refers to the crystalline phase with the most crystalline phase among the main crystalline phases identified by the peak of the X-ray diffraction spectrum of the crystallized glass, that is, the crystalline phase with the first and second most crystalline phases. It can be α-white silica as the main crystalline phase with the first most, or it can be lithium disilicate as the main crystalline phase with the first most.
[0058] The crystallized glass may further contain one or more other crystalline phases selected from petalite, virgilite, quartz, and lithium monosilicate crystals. These crystalline phases are preferably contained in a small amount or not contained.
[0059] Crystallized glass containing α-cristobalite and lithium disilicate as main crystal phases is obtained by heat-treating and crystallizing a raw glass having the following composition.
[0060] The composition of the crystallized glass is, in terms of mass % converted to oxides:
[0061] The content of SiO2 component is 65.0% to 85.0%;
[0062] The content of Al2O3 component is 1.5% to 5.9%;
[0063] The content of P2O5 component is greater than 0% and less than 5.0%;
[0064] The content of Li2O component is 5.0% to 10.8%; and
[0065] The content of ZrO2 component is 4.0% to 12.5%; and
[0066] [(SiO2 content + Li2O content) / Al2O3 content] is greater than 13.9.
[0067] In particular, by setting the contents of SiO2, Al2O3, and Li2O to the above ranges, a predetermined crystalline phase can be obtained. If the Al2O3 content is greater than the above upper limit, a lithium aluminum silicate crystalline phase is easily generated, and if the SiO2 and Li2O components are outside the above ranges, lithium disilicate is not formed and only α-white silica is easily generated.
[0068] SiO2 component is the skeleton component that constitutes crystallized glass, based on improving stability, and the purpose that required crystalline phase is separated out, it is required essential component.By making the content of SiO2 component below 85.0%, can suppress the excessive promotion of viscosity, the deterioration of solubility, in addition, by making it more than 65.0%, can promote the stability of crystallized glass.
[0069] Therefore, the upper limit is preferably 85.0% or less, more preferably 83.0% or less, and even more preferably 80.0% or less. In addition, the lower limit is preferably 65.0% or more, more preferably 68.0% or more, and even more preferably greater than 70.0%.
[0070] Al2O3 component is the skeleton component of crystallized glass, and is a necessary component for the purpose of improving stability. If the content of Al2O3 component is below 5.9%, the transmittance at 450nm can be improved, and devitrification can be suppressed. In addition, if it is set to more than 1.5%, stability can be suppressed.
[0071] Therefore, the upper limit is preferably 5.9% or less, more preferably 5.5% or less, and still more preferably 5.3% or less. In addition, the lower limit is preferably 1.5% or more, more preferably 1.8% or more, and still more preferably 2.0% or more.
[0072] P2O5 is an essential component for promoting the crystallization of crystallized glass. If the content of P2O5 is below 5.0%, the phase separation of glass can be suppressed. In addition, if it is 0%, the desired crystal phase cannot be obtained.
[0073] Therefore, the upper limit is preferably 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. The lower limit is preferably greater than 0%, more preferably 0.5% or more, and even more preferably 1.0% or more.
[0074] The Li2O component is a necessary component for the purpose of improving the melting property of the blank glass, improving the manufacturability, and precipitating the desired crystalline phase. If the content of the Li2O component is 10.8% or less, the devitrification can be suppressed. In addition, if it is 5.0% or more, the viscosity deterioration and the melting property deterioration can be suppressed, and the manufacturability can be improved. In addition, the desired crystalline phase can be obtained.
[0075] Therefore, the upper limit is preferably set to 10.8% or less, more preferably to 10.5% or less, for example, it can be set to 10.2% or less, 8.9% or less, or 8.5% or less. In addition, the lower limit is preferably set to 5.0% or more, more preferably to 6.2% or more, and even more preferably to 7.0% or more, for example, it can be set to 8.1% or more, or 9.0% or more.
[0076] The ZrO2 component is a component that becomes a nucleating agent for crystallization. If the content of the ZrO2 component is 12.5% or less, the deterioration of solubility can be suppressed. If the content of the ZrO2 component is 4.0% or more, it is easy to improve the transmittance at 450nm.
[0077] Therefore, the upper limit is preferably set to 12.5% or less, for example, it can be set to 12.0% or less, 11.5% or less, 11.0% or less, 10.0% or less, or 9.0% or less. In addition, the lower limit is preferably set to 4.0% or more, more preferably to 4.7% or more, more preferably to 5.7% or more, and more preferably to more than 6.9%, for example, it can be set to more than 7%, or more than 10.5%.
[0078] The MgO component is an optional component. Even if it is 0%, the glass of the present invention can be manufactured. However, when its content is greater than 0%, the low temperature melting property can be improved. In the present invention, the optional component refers to a component that may or may not be included. If the content of the MgO component is 5.0% or less, it becomes easy to strengthen during chemical strengthening.
[0079] Therefore, the upper limit is preferably 5.0% or less, more preferably 3.0% or less, and even more preferably less than 2.0%. In addition, the lower limit is preferably 0% or more, more preferably 0.1% or more, and even more preferably 0.2% or more.
[0080] The ZnO component is an optional component. Even if it is 0%, the glass of the present invention can be produced. However, when the content is greater than 0%, the low temperature melting property can be improved. When the content of the ZnO component is 5.0% or less, strengthening becomes easy during chemical strengthening.
[0081] Therefore, the upper limit is preferably 5.0% or less, more preferably 3.0% or less, and even more preferably less than 2.0%. In addition, the lower limit is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.2% or more.
[0082] The CaO component is an optional component, and the glass of the present invention can be produced even if it is 0%, but the low temperature melting property can be improved when the content is greater than 0%. When the content of the CaO component is 5.0% or less, strengthening becomes easy during chemical strengthening.
[0083] Therefore, the upper limit is preferably 5.0% or less, more preferably 3.0% or less, and even more preferably less than 1.0%. In addition, the lower limit is preferably greater than 0%, more preferably 0.1% or more, even more preferably 0.2% or more, and even more preferably 0.3% or more.
[0084] The K2O component and the Na2O component are arbitrary components that improve the meltability of the rough glass and improve the manufacturability. If the content of the K2O component and the Na2O component is 5.0% or less, respectively, the devitrification can be suppressed. In addition, even if the K2O component and the Na2O component are 0%, the glass of the present invention can be manufactured. However, when the content is greater than 0%, the viscosity deterioration and the meltability deterioration can be suppressed, and the manufacturability can be improved.
[0085] Therefore, the Na2O component preferably has an upper limit of 5.0% or less, more preferably 4.0% or less, still more preferably less than 3.0%, and still more preferably less than 2.0%. In addition, the lower limit is preferably 0% or more, more preferably 0.2% or more, and still more preferably 0.3% or more.
[0086] The upper limit of the K2O component is preferably set to 5.0% or less, more preferably to 4.0% or less, for example, it can be set to 3.0% or less, 2.0% or less, or 1.0% or less. In addition, the lower limit is preferably set to 0% or more, more preferably to 0.2% or more, and even more preferably to 0.3% or more, for example, it can be set to 0.5% or more, 1.0% or more, 2.0% or more, 2.5% or more, or 3.0% or more.
[0087] The Sb2O3 component is an arbitrary component that plays the role of a clarifier when manufacturing rough glass. If the Sb2O3 component is contained in excess, there is a risk that the transmittance in the short wavelength region of the visible light region will deteriorate. Therefore, it is preferred that the upper limit is set to 3.0% or less, more preferably to 2.0% or less, even more preferably to 1.0% or less, even more preferably to 0.6% or less, and even more preferably to 0.5% or less. It is preferred that the lower limit is set to 0% or more, more preferably to 0.01% or more, and even more preferably to 0.03% or more.
[0088] The B2O3 component is an arbitrary component having the effect of reducing the viscosity of the rough glass. If the content of the B2O3 component is 5.0% or less, the devitrification can be suppressed. In addition, even if the content of the B2O3 component is 0%, the glass of the present invention can be manufactured, but when the content is greater than 0%, the viscosity and meltability of the rough glass can be suppressed.
[0089] Therefore, the upper limit is preferably 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. In addition, the lower limit is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.3% or more.
[0090] TiO2 component is an arbitrary component having the effect of improving the refractive index. If the content of TiO2 component is below 5.0%, devitrification can be suppressed. In addition, even if the content of TiO2 component is 0%, the glass of the present invention can be manufactured, but when the content is greater than 0%, the refractive index can be improved.
[0091] Therefore, the upper limit is preferably 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. In addition, the lower limit is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.3% or more.
[0092] The Gd2O3 component is an arbitrary component having an effect of increasing the refractive index. If the content of the Gd2O3 component is 5.0% or less, devitrification can be suppressed. In addition, even if the content of the Gd2O3 component is 0%, the glass of the present invention can be manufactured, but when the content is greater than 0%, the refractive index can be increased.
[0093] Therefore, the upper limit is preferably 5.0% or less, more preferably 4.5% or less, and even more preferably 4.0% or less. In addition, the lower limit is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.3% or more.
[0094] The Nb2O5 component is an arbitrary component having the effect of increasing the refractive index. If the content of the Nb2O5 component is 3.0% or less, the devitrification can be suppressed. In addition, even if the content of the Nb2O5 component is 0%, the glass of the present invention can be manufactured, but when the content is greater than 0%, the refractive index can be increased.
[0095] Therefore, the upper limit is preferably 3.0% or less, more preferably 2.0% or less, and even more preferably 1.0% or less. In addition, the lower limit is preferably 0% or more, more preferably greater than 0%, even more preferably 0.1% or more, and even more preferably 0.3% or more.
[0096] SrO and BaO are arbitrary components, and the glass of the present invention can be produced even if they are 0%, but when the content is greater than 0%, the low temperature melting property can be improved. If the content of SrO and BaO is less than 5.0%, it becomes easy to strengthen during chemical strengthening.
[0097] Therefore, the upper limits of the SrO component and the BaO component can be preferably set to 5.0% or less, more preferably 3.0% or less, and still more preferably 1.0% or less.
[0098] By setting the total content of CaO and MgO components [CaO content + MgO content] to 5.0% or less, difficulty in chemical strengthening can be avoided. Even at 0%, the glass of the present invention can be produced. However, when the content exceeds 0%, deterioration of solubility can be suppressed.
[0099] Therefore, the upper limit of [the content of the CaO component + the content of the MgO component] is preferably set to 5.0% or less, more preferably to 3.0% or less, even more preferably to less than 3.0%, and even more preferably to 1.0% or less.
[0100] Furthermore, the lower limit of [the content of the CaO component + the content of the MgO component] is preferably set to 0% or more, more preferably set to 0.1% or more, and still more preferably set to 0.2% or more.
[0101] Even if the total content of K2O and Na2O is 0% [the content of K2O + the content of Na2O], the glass of the present invention can be produced. However, when the content is greater than 0%, the viscosity can be suppressed from deteriorating and the melting temperature can be suppressed from increasing. In addition, by making it 5.0% or less, the devitrification can be suppressed from deteriorating.
[0102] Therefore, the upper limit of [the content of the K2O component + the content of the Na2O component] is preferably set to 5.0% or less, more preferably to 4.0% or less, still more preferably to less than 4.0%, still more preferably to less than 3.0%, and further preferably to less than 2.0%. In addition, the lower limit is preferably set to 0% or more, more preferably to 0.2% or more, and still more preferably to 0.3% or more.
[0103] By setting [(the content of SiO2 component + the content of Li2O component) / the content of Al2O3 component] to be greater than 13.9, α-cristobalite and lithium disilicate as the main crystalline phase can be generated.
[0104] Therefore, the upper limit of [(the content of SiO2 component + the content of Li2O component) / the content of Al2O3 component] is preferably set to 50.0 or less, more preferably to 48.0 or less, and even more preferably to 45.0 or less. In addition, the lower limit is preferably set to greater than 13.9, more preferably to 14.5 or more, and even more preferably to 15.0 or more.
[0105] [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] can also be set to less than 0.88. By setting it to less than 0.88, it becomes easy to generate α-white silica and lithium disilicate as the main crystal phase.
[0106] Therefore, it is preferred that the upper limit of [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] be less than 0.88, more preferably be 0.87 or less, and even more preferably be 0.85 or less. In addition, it is preferred that the lower limit be 0.10 or more, more preferably be 0.15 or more, and even more preferably be 0.20 or more.
[0107] [(content of P2O5 component + content of K2O component + content of MgO component + content of Al2O3 component) / content of ZrO2 component] can also be set to less than 1.32. By setting it to less than 1.32, it becomes easy to generate α-white silica and lithium disilicate as the main crystalline phase.
[0108] Therefore, it is preferred that the upper limit of [(content of P2O5 component + content of K2O component + content of MgO component + content of Al2O3 component) / content of ZrO2 component] be less than 1.32, more preferably 1.28 or less, and even more preferably 1.25 or less. In addition, the lower limit is preferably 0.2 or more, more preferably 0.3 or more, and even more preferably 0.4 or more.
[0109] It is also possible to set [the content of Al2O3 component / the content of ZrO2 component] to be greater than 0 and less than 1.0. By setting it to less than 1.0, it is easy to obtain the desired crystal phase, and by setting it to greater than 0, it becomes easy to suppress the devitrification deterioration.
[0110] Therefore, it is preferred that the upper limit of [the content of Al2O3 component / the content of ZrO2 component] be set to 1.0 or less, more preferably 0.9 or less, and even more preferably 0.8 or less. In addition, the lower limit is preferably set to greater than 0, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0111] The content of [Li2O component + Al2O3 component] can also be set to 6.5% to 15.5%. By setting it to 15.5% or less, it becomes easy to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to 6.5% or more, the desired crystal phase can be obtained and the glass can be easily stabilized.
[0112] Therefore, the upper limit of [Li2O content + Al2O3 content] is preferably set to 15.5% or less, more preferably 15.0% or less, and even more preferably 14.0% or less. In addition, the lower limit is preferably set to 6.5% or more, more preferably 8.0% or more, and even more preferably 10.0% or more.
[0113] [(Li2O content + Al2O3 content) / ZrO2 content] can also be set to 1.0 to 2.7. By setting it to 2.7 or less, it becomes easy to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to 1.0 or more, the desired crystal phase can be obtained and it becomes easy to stabilize the glass.
[0114] Therefore, it is preferred that the upper limit of [(Li2O content + Al2O3 content) / ZrO2 content] be set to 2.7 or less, more preferably 2.4 or less, and even more preferably 2.1 or less. In addition, the lower limit is preferably set to 1.0 or more, more preferably 1.3 or more, and even more preferably 1.6 or more.
[0115] It is also possible to set [the content of SiO2 component / (the content of P2O5 component+the content of Li2O component+the content of Na2O component+the content of K2O component)] to 4.5 or more. By setting it to 4.5 or more, it is easy to obtain the desired crystal phase.
[0116] Therefore, the lower limit is preferably set to 4.5 or more, and more preferably set to 5.0 or more. In addition, by setting [the content of SiO2 component / (the content of P2O5 component+the content of Li2O component+the content of Na2O component+the content of K2O component)] to 20.0 or less, the desired crystalline phase can be precipitated, and the excessive increase of viscosity and the deterioration of solubility can be suppressed. Therefore, the upper limit of [the content of SiO2 component / (the content of P2O5 component+the content of Li2O component+the content of Na2O component+the content of K2O component)] can be set to, for example, less than 20.0, less than 10.0, or less than 7.5.
[0117] [Content of K2O component / Content of ZrO2 component] can also be set to be greater than 0 to less than 0.5. By setting it to less than 0.5, it becomes easy to obtain the desired crystal phase, and by setting it to greater than 0, it is possible to suppress the deterioration of viscosity and meltability, and it becomes easy to improve the manufacturability.
[0118] Therefore, the upper limit of [the content of K2O component / the content of ZrO2 component] is preferably set to less than 0.5, more preferably to 0.4 or less, and even more preferably to 0.3 or less. In addition, the lower limit is preferably set to greater than 0, and more preferably to 0.1 or more.
[0119] It is also possible to set [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] to be greater than 0 and less than 0.85. By setting it to less than 0.85, it becomes easy to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to greater than 0, it is easy to stabilize the glass.
[0120] Therefore, it is preferred that the upper limit of [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] be set to 0.85 or less, more preferably 0.80 or less, and even more preferably 0.75 or less. In addition, the lower limit is preferably set to greater than 0, more preferably 0.1 or more, and even more preferably 0.2 or more.
[0121] It is also possible to set [(content of K2O component + content of Al2O3 component) / (content of ZnO component + content of ZrO2 component)] to a value greater than 0 and less than 0.95. By setting it to less than 0.95, it becomes easier to suppress the formation of lithium aluminum silicate crystal phase, and by setting it to greater than 0, it becomes easier to stabilize the glass.
[0122] Therefore, it is preferred that the upper limit of [(content of K2O component + content of Al2O3 component) / (content of ZnO component + content of ZrO2 component)] is set to 0.95 or less, more preferably to 0.90 or less, and even more preferably to 0.85 or less. In addition, the lower limit is preferably set to greater than 0, more preferably to 0.1 or more, and even more preferably to 0.2 or more.
[0123] The crystallized glass of the present invention may include Bi2O3, Cr2O3, CuO, La2O3, MnO, MoO3, PbO, V2O5, WO3, Y2O3 and other components, or may not include these components, without including these components, thereby preventing the transmittance from deteriorating.
[0124] Further in the crystallized glass, other components not mentioned above may be included or not included within the range that does not damage the properties of the crystallized glass of the present invention. For example, metal components such as Yb, Lu, Fe, Co, Ni, and Ag (including their metal oxides) etc. may be listed.
[0125] In addition, as a clarifier of the glass, in addition to the Sb2O3 component, a SnO2 component, a CeO2 component, an As2O3 component, and one or more selected from the group consisting of F, NOx, and SOx may be included, or not included. The upper limit of the content of the clarifier may preferably be set to 3.0% or less, more preferably 2.0% or less, still more preferably 1.0% or less, and most preferably 0.6% or less.
[0126] On the other hand, each of Pb, Th, Tl, Os, Be, Cl, and Se is considered as a harmful chemical substance in recent years and its use tends to be avoided, so it is preferable that these components are not substantially contained.
[0127] The Vickers hardness (Hv0.2: Hv at a test load of 200 gf) of the crystallized glass of the present invention is preferably set to 630 or more, more preferably set to 690 or more, and even more preferably set to 710 or more. The Vickers hardness tends to increase by reducing the ZrO2 component, increasing the Li2O component, or reducing the K2O component.
[0128] The crystallized glass of the present invention has a transmittance of 0% to 80% at a wavelength of 450nm when the thickness is 1mm, and can be set to be, for example, 20% or more, 30% or more, or 50% or more. In addition, it can also be set to be less than 20%. The transmittance can be adjusted by the content of ZrO2 component, Li2O component, or K2O component, etc.
[0129] The crystallized glass of the present invention can be produced by the following method. Specifically, raw materials are uniformly mixed so that each component is within a predetermined content range, and then melted and molded to produce a blank glass. Then, the blank glass is crystallized to produce a crystallized glass.
[0130] The heat treatment for crystallization can be performed in one step or in two steps.
[0131] In the two-step heat treatment, a nucleation step is first performed by heat treatment at a first temperature, and after the nucleation step, a crystal growth step is performed by heat treatment at a second temperature higher than the nucleation step.
[0132] The first temperature of the two-step heat treatment is preferably set to 400 to 680° C., more preferably 450 to 650° C., and even more preferably 500 to 600° C. The holding time at the first temperature is preferably 30 to 2000 minutes, more preferably 180 to 1440 minutes.
[0133] The second temperature of the two-step heat treatment is preferably 680° C. or higher, for example 700° C. to 800° C., preferably 700° C. to 750° C. The holding time at the second temperature is preferably 30 to 600 minutes, more preferably 60 to 400 minutes.
[0134] In a one-stage heat treatment, the nucleation step and the crystal growth step are performed continuously at a temperature of one stage. Usually, the temperature is raised to a predetermined heat treatment temperature, and after reaching the heat treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered.
[0135] When performing a one-step heat treatment, the heat treatment temperature is preferably 680° C. or higher, for example, 700° C. to 800° C., preferably 700° C. to 750° C. The holding time at the heat treatment temperature is preferably 30 to 500 minutes, more preferably 60 to 400 minutes.
[0136] A compressive stress layer can also be formed on the surface by strengthening the crystallized glass. As a method for forming a compressive stress layer in the strengthened crystallized glass, for example, there is a chemical strengthening method in which an alkaline component present in the surface layer of the crystallized glass is exchanged with an alkaline component having an ion radius larger than that of the alkaline component to form a compressive stress layer on the surface layer.
[0137] The chemical strengthening method can be implemented, for example, by the following steps. The crystallized glass is contacted with or immersed in a salt containing potassium or sodium, such as potassium nitrate (KNO3), sodium nitrate (NaNO3) or a molten salt of a mixed salt or a composite salt thereof. The treatment of contacting or immersing in the molten salt (chemical strengthening treatment) can be performed in one step or in two steps.
[0138] When a one-step chemical strengthening treatment is performed, for example, the material is contacted with or immersed in a salt containing potassium or sodium, or a mixed salt thereof, heated at 350° C. to 550° C. for 1 minute to 1440 minutes.
[0139] In the case of a two-step chemical strengthening treatment, for example, in the first step, the mixture is contacted or immersed in a sodium salt or a mixed salt of a potassium salt and a sodium salt heated at 350° C. to 550° C. for 1 minute to 1440 minutes, preferably for 30 minutes to 1000 minutes. Then, in the second step, the mixture is contacted or immersed in a potassium salt or a mixed salt of a potassium salt and a sodium salt heated at 350° C. to 550° C. for 1 minute to 1440 minutes, preferably for 60 minutes to 600 minutes.
[0140] The present invention includes lithium disilicate as the main crystalline phase, and can perform two-step chemical strengthening by exchanging lithium with sodium and then exchanging sodium with potassium. By such two-step chemical strengthening, the compressive stress value of the outermost surface can be increased.
[0141] The compressive stress value (CS) of the outermost surface of the strengthened crystallized glass is preferably 400MPa or more, more preferably 500MPa or more. The depth (DOLzero) when the compressive stress of the compressive stress layer is 0MPa is preferably 120μm or more, more preferably 130μm or more. The central tensile stress (CT) can be, for example, 30MPa or more or 40MPa or more.
[0142] Examples 1 to 27, Comparative Example 1, Comparative Example 2
[0143] 1. Manufacture of crystallized glass
[0144] As raw materials for each component of the crystallized glass, corresponding oxides, hydroxides, carbonates, nitrates, fluorides, chlorides, metaphosphate compounds and the like are selected, and these raw materials are weighed and uniformly mixed in a manner to form the compositions described in Tables 1 to 4. Comparative Example 1 is Example 9 of Patent Document 2.
[0145] It should be noted that (Si+Li) / Al in the table is the abbreviation of [(the content of SiO2 component + the content of Li2O component) / the content of Al2O3 component], (K+Al) / Zr is the abbreviation of [(the content of K2O component + the content of Al2O3 component) / the content of ZrO2 component], and (P+K+Mg+Al) / Zr is the abbreviation of [(the content of P2O5 component + the content of K2O component + the content of MgO component + the content of Al2O3 component) / the content of ZrO2 component].
[0146] Next, the mixed raw materials are put into a platinum crucible and melted in an electric furnace at 1300°C to 1600°C for 2 to 24 hours according to the melting difficulty of the glass composition. Then, the molten glass is stirred and homogenized, and then cooled to 1000°C to 1450°C, and cast into a mold, and slowly cooled to make a blank glass. The obtained blank glass is heated under the crystallization conditions shown in Tables 1 to 4 to make a crystallized glass.
[0147] The crystal phase of crystallized glass is to be distinguished by the angle of the peak appearing in the X-ray diffraction spectrum using an X-ray diffraction analysis device (Bruker Corporation system, D8Discover). The crystal phase separated out is recorded in Table 1 to Table 4. It should be noted that cri. in the table is the abbreviation of α-white silica, LS2 is the abbreviation of lithium disilicate, LS is the abbreviation of lithium monosilicate crystal, Quartz is the abbreviation of crystal (quartz), and Petalite is the abbreviation of petalite (leaf feldspar). In all embodiments, the main crystal phase is α-white silica and lithium disilicate.
[0148] 2. Evaluation of crystallized glass
[0149] The produced crystallized glass was cut and ground to prepare samples, and the samples were evaluated as follows. The results are shown in Tables 1 to 4.
[0150] (1) Transmittance (λ5, λ80)
[0151] The light transmittance including reflection loss at a thickness of 1 mm was measured using a spectrophotometer (U-4000, manufactured by Hitachi Advanced Technologies Co., Ltd.), and the wavelength (λ5) at which the transmittance was 5% and the wavelength (λ80) at which the transmittance was 80% were determined.
[0152] (2) Transmittance
[0153] The light transmittance including reflection loss at 450 nm with a thickness of 1 mm was measured using a spectrophotometer (U-4000, manufactured by Hitachi Advanced Technologies Corporation).
[0154] (3) Vickers hardness (Hv0.2)
[0155] Using a diamond quadrangular pyramid indenter with an opposite angle of 136°, the load when a pyramid-shaped depression is pressed on the sample surface is divided by the surface area (mm) calculated based on the length of the depression. 2 The hardness was measured using a micro Vickers hardness tester HMV-G21D manufactured by Shimadzu Corporation with a test load of 200 gf and a holding time of 10 seconds.
[0156] 3. Chemical strengthening
[0157] A crystallized glass having the following composition (mass %) was used as Comparative Example 2. The crystallized glass contained petalite as a main crystalline phase and lithium disilicate.
[0158] The SiO2 component is set to 78.3%, the Al2O3 component is set to 8.1%, the B2O3 component is set to 0.2%, the Li2O component is set to 11.9%, the Na2O component is set to 1.7%, the K2O component is set to 0.0%, the ZnO component is set to 0.0%, the ZrO2 component is set to 4.0%, and the P2O5 component is set to 2.2%.
[0159] In Example 8, Example 24, Example 27, Comparative Example 2, the crystallized glass manufactured was cut and ground to obtain a crystallized glass substrate having a material thickness (base material thickness) as shown in Table 5. Using this crystallized glass substrate as a mother material, and strengthening for the first time (first stage) and strengthening for the second time (second stage) were performed under the conditions as shown in Table 5 to obtain strengthened crystallized glass.
[0160] For the tempered crystallized glass, the compressive stress value (CS [MPa]) of the outermost surface was measured using a glass surface stress meter FSM-6000L series manufactured by Orihara Seisakusho. A light source with a wavelength of 596 nm was used as the light source of the measuring machine. The photoelastic coefficient at a wavelength of 596 nm was 28.2 as a representative value in the examples, and 26.2 as a representative value in the comparative examples. The results are shown in Table 5.
[0161] The depth (DOLzero [μm]) of the compressive stress layer when the compressive stress is 0 MPa and the central tensile stress (CT [(MPa)]) were measured using a scattered light photoelastic stress meter (manufactured by Orihara Seisakusho, Ltd.) . A light source with a wavelength of 518 nm was used as the measurement light source. The photoelastic coefficient at a wavelength of 518 nm was 28.8 as a representative value in the examples and 26.6 as a representative value in the comparative examples. The results are shown in Table 5.
[0162] [Table 1]
[0163]
[0164] [Table 2]
[0165]
[0166] [Table 3]
[0167]
[0168] [Table 4]
[0169]
[0170] [Table 5]
[0171]
[0172] Above, several embodiments and / or examples of the present invention have been described in detail, and those skilled in the art can easily make various changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these various changes are also included in the scope of the present invention.
[0173] The contents of the documents described in this specification and the Japanese application specification which is the basis of the Paris Convention priority claim of the present invention are incorporated herein by reference in their entirety.
Claims
1. A crystallized glass comprising: α-white silica as a main crystal phase, and lithium disilicate; Calculated in mass % of oxide conversion: The content of SiO2 component is 65.0% to 85.0%; The content of Al2O3 component is 1.5% to 5.9%; The content of P2O5 component is greater than 0% and less than 5.0%; The content of Li2O component is 5.0% to 10.8%; and The content of ZrO2 component is 4.0% to 12.5%; Furthermore, [(the content of SiO2 component + the content of Li2O component) / the content of Al2O3 component] is greater than 13.
9.
2. The crystallized glass according to claim 1, wherein Calculated in mass % of oxide conversion: The content of B2O3 component is 0% to 5.0%; The content of Na2O component is 0% to 5.0%; The content of K2O component is 0% to 5.0%; The content of MgO component is 0% to 5.0%; The content of CaO component is 0% to 5.0%; The content of ZnO component is 0% to 5.0%; The content of TiO2 component is 0% to 5.0%; The content of Gd2O3 component is 0% to 5.0%; The content of Sb2O3 component is 0% to 3.0%; and The content of Nb2O5 component is 0% to 3.0%.
3. The crystallized glass according to claim 1 or 2, wherein: The content of ZrO2 component is 4.7% to 12.5%.
4. The crystallized glass according to claim 1 or 2, wherein: The content of ZrO2 component is greater than 7% and less than 12.5%.
5. The crystallized glass according to claim 1 or 2, wherein: Calculated in mass % of oxide conversion: [(content of K2O component + content of Al2O3 component) / content of ZrO2 component] is less than 0.
88.
6. The crystallized glass according to claim 1 or 2, wherein: Calculated in mass % of oxide conversion: [(content of P2O5 component + content of K2O component + content of MgO component + content of Al2O3 component) / content of ZrO2 component] is less than 1.
32.
7. The crystallized glass according to claim 1 or 2, wherein: There is a compressive stress layer on the surface.
8. The crystallized glass according to claim 1 or 2, wherein: This crystallized glass can be used for glass components of smartphones.
Citation Information
Patent Citations
High strength glass-ceramics having petalite and lithium silicate structures
JP2021095333A
Glass-ceramics and tempered glass-ceramics
JP2022044054A